Persuasive preaching : a biblical and practical guide to the effective use of persuasion - Overstreet, R. Larry (Lexham Press, 2018)
"Michael Dudit, executive editor of Preaching Magazine, writes in the foreword that'the reader will find in this book a valuable discussion of what persuasion really is, what the Bible has to say about it, how it is modeled in the New Testament, and what role persuasion should and should not play in our own preaching in the twenty-first century. The author has provided solid biblical content and practical guidance that will be a powerful resource for preachers and church leaders. He writes with clarity and—dare I say it?—persuasive power. I hope you will be as blessed by this book as I have been.'"--Publisher.